2018
DOI: 10.3390/nu11010020
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militaris Grown on Germinated Soybean Suppresses KRAS-Driven Colorectal Cancer by Inhibiting the RAS/ERK Pathway

Abstract: Cordyceps militaris is a commonly used medicinal mushroom containing various therapeutic effects such as anti-inflammatory, anti-allergic, and anti-cancer activities. This study examined whether Cordyceps militaris on germinated soybeans (GSC) has a suppressive effect on a v-ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS)-driven colorectal cancer which is notorious for its un-druggable features and the ineffectiveness of conventional therapies against it. GSC extract was prepared and its proximate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…CM possess multi-functions of enhancing immunity, anti-inflammatory and antioxidant with fewer adverse effects, foe it’s enriched in active ingredients such as cordyceps polysaccharide, D-mannitol, and cordycepin, etc. ( Wang et al, 2012 ; Seo et al, 2018 ). Currently, artificial culture of CM has greatly increased its production and lowered its cost ( Dong et al, 2015 ; Lou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…CM possess multi-functions of enhancing immunity, anti-inflammatory and antioxidant with fewer adverse effects, foe it’s enriched in active ingredients such as cordyceps polysaccharide, D-mannitol, and cordycepin, etc. ( Wang et al, 2012 ; Seo et al, 2018 ). Currently, artificial culture of CM has greatly increased its production and lowered its cost ( Dong et al, 2015 ; Lou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, CM had little effect on nonprostatic human endometrial epithelial cells. It is reported that Cordyceps militaris extract inhibited the proliferation of breast cancer, ovarian cancer, nonsmall-cell lung cancer, and colorectal cancer cells through androgen-independent signaling pathways [ 22 , 23 , 24 , 25 ]. Given that the CM-induced decrease in prostate hyperplasia was independent of the serum level of testosterone, CM may regulate the proliferation of prostate cells by inhibiting the activation of intracellular signal pathways other than those involved in testosterone signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited studies have examined the effects of natural extracts targeting mutated KRAS-driven CRC and none of these studies tested the efficacy of these extracts on muscle function. In our previous study, Cordyceps militaris germinated soybeans suppressed mutated KRAS-driven CRC via the RAS/ERK pathway [14]. Phellinus linteus grown on germinated brown rice increased the sensitivity of Cetuximab to inhibit KRAS-CRC progression both in vitro and in vivo [15].…”
Section: Introductionmentioning
confidence: 90%
“…Western blot analysis was performed in triplicate as previously described [14]. Cells were treated with compound PN (0.5-4 µg/mL) for 48 h and detached with trypsin-EDTA.…”
Section: Western Blottingmentioning
confidence: 99%